2005
DOI: 10.1063/1.2123383
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sb in the growth and optical properties of 1.55μm GaInN(Sb)As∕GaNAs quantum-well structures by molecular-beam epitaxy

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=12744131&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=12744131&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…This finding could explain and support the optical properties reported by H.D. Sun et al [21] that they attribute to the influence of segregated Sb on the energy profile across the QW. Fig.…”
Section: Resultssupporting
confidence: 84%
“…This finding could explain and support the optical properties reported by H.D. Sun et al [21] that they attribute to the influence of segregated Sb on the energy profile across the QW. Fig.…”
Section: Resultssupporting
confidence: 84%
“…Qualitatively the behavior was similar for samples B-D, regardless of Sb content. More detailed spectroscopic studies of these samples were reported recently [20]. Table 2 provides a quantitative comparison between the PL results for the four samples.…”
Section: Article In Pressmentioning
confidence: 98%
“…The use of a surfactant is one option for reducing surface roughness for higher concentrations of nitrogen. Antimony is one option as a surfactant [1,2], and recently bismuth has begun to attract attention as a potential surfactant for dilute nitride growth [3,4]. A recent study [3] also indicates that bismuth may dramatically alter N incorporation besides acting as a surfactant, although this study only considered low (0.4-0.95%) nitrogen concentrations.…”
mentioning
confidence: 94%